Changed Human Values in India and Pollution: Analysis of Some Contemporary Issues (Global Journal of Human-Social Science, 2012)
Environmental Pollution (Pollution) is a global issue. Though responsibility of India in creating Pollution is less as compared to developed countries, however we cannot deny our role as we shall be largest population country and 4th largest economy soon. Pollution is the problem that is purely created by human beings and human behavior is the main cause of this act. Behavior is governed by values. This paper addresses a theoretical study of impact of human values on pollution in the context of Indian Society.
Keywords: Human Values; Pollution; Indian Society